Functional Limb Salvage Following a 24-Hour-Delayed Fasciotomy for Pediatric Hand Compartment Syndrome: A Case Report - Rohman Sungkono; Adri Yandra Hidayat; Andrea Valentino; Ade Wirdayanto; Arip Heru Tripana (HM Publisher, 2025)
Background: Acute compartment syndrome (ACS) in the pediatric hand is a formidable surgical emergency where delayed diagnosis can lead to devastating neuromuscular deficits and limb loss. The narrow therapeutic window, often termed the